High-income export destinations, quality and wages - Brambilla, María Irene (2016)
This paper establishes a link between the income level of the destination countries and the level of average wages in the exporting country across the world economy. We use cross-country panel data to set up an instrumental variable model of high-income export destinations and wages. We find robust evidence that, worldwide, industries that ship products to high-income destinations do pay higher average wages. Our IV results indicate this is a causal relationship. We also explore the operating mechanisms, and find robust evidence in support of a dual link. First, industries that ship products to high-income destination export higher quality goods (as measured by the average unit value of exports within industries). This is because high-income countries demand high-quality products. Second, the provision of quality is costly and requires more intensive use of higher-wage skilled labor. As a result, the production of higher quality products at the industry level creates a wage premium and conduces to higher average industry wages.